PHILANTHROPIC DA’WAH ON SOCIAL MEDIA: INFLUENCE ON CHARITABLE ATTITUDES OF URBAN MUSLIMS IN BANDAR LAMPUNG - Makmun, Fariza; Nasution, Nadya Amalia; Brodard, Baptiste (AKADEMIKA: Jurnal Pemikiran Islam, 2026)
Digital philanthropic da’wah on social media has emerged as a significant force shaping charitable engagement among urban Muslim communities; yet, the psychological mechanisms through which media exposure translates into attitudinal change remain underexplored in the Indonesian context. Grounded in the Stimulus-Organism-Response (S-O-R) theoretical framework, this study examines how exposure to digital philanthropic da’wah influences the charitable attitudes of urban Muslims in Bandar Lampung. Employing a convergent mixed-methods design, the study integrates a quantitative survey of 100 respondents drawn from the BAZNAS Bandar Lampung donor database with in-depth interviews of 15 purposively selected participants. Regression analysis reveals a significant positive effect of digital da’wah exposure on charitable attitudes (β = 0.581, R² = 0.338, F = 49.982, p < 0.001), with the strongest influence found in the cognitive dimension (R² = 32.4%), followed by affective (R² = 28.0%) and conative aspects (R² = 22.7%). Qualitative findings uncover five key themes: emotional resonance with content, credibility concerns, motivation for social engagement, heightened awareness, and perceived ease of donating. This study contributes a dual-perspective S-O-R analysis of Islamic digital philanthropy in a mid-sized Indonesian city, demonstrating that cognitive awareness is the primary mechanism of attitude formation while conative conversion remains constrained by institutional trust deficits. These findings offer strategic guidance for Islamic philanthropic organizations and digital da'i seeking to design credible, informationally rich, and behaviorally effective campaigns